PENGARUH MOTIVASI DAN PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA GURU DI ERA PANDEMI COVID-19 PADA SMK TEKNOLOGI WIRA BHAKTI DENPASAR - Ni Wayan Diah Marliani; Ni Luh Sili Antari (Journal Research of Management, 2021)
The world of education plays an important role in an effort to make the nation's future generations of quality. This can happen if it is supported by good teacher performance. Factors that influence teacher performance include motivation and use of information technology. The objectives of this study are: to determine the effect of motivation on teacher performance in the Covid-19 pandemic era at Wira Bhakti Technology Vocational School Denpasar, to determine the effect of using information technology on teacher performance in the Covid-19 pandemic era at SMK Teknologi Wira Bhakti Denpasar, to determine how much the influence of motivation and the use of information technology on teacher performance in the era of the Covid-19 pandemic at SMK Teknologi Wira Bhakti Denpasar. The sample used amounted to 52 people with a sampling technique that is saturated sampling. The analysis technique used: descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, t-test analysis, and determination analysis using SPSS Version 24.0 application. The results showed that: 1) partially motivation has a positive and significant effect on teacher performance in the Covid-19 pandemic era at SMK Teknologi Wira Bhakti Denpasar, 2) the use of information technology partially has a positive and significant effect on teacher performance in the Covid pandemic era. -19 at Wira Bhakti Technology Vocational School Denpasar, 3) the magnitude of the influence of motivation and the use of information technology on teacher performance in the Covid-19 pandemic era at Wira Bhakti Technology Vocational School Denpasar was 61.9% while the remaining 38.1% was influenced by other variables which was not discussed in this study. Suggestions can be conveyed so that the school always pays attention to motivation and the use of information technology because together these variables can improve teacher performance.